2011
DOI: 10.1016/j.actpsy.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced perception of various linguistic features by musicians: A cross-linguistic study

Abstract: Two cross-linguistic experiments comparing musicians and non-musicians were performed in order to examine whether musicians have enhanced perception of specific acoustical features of speech in a second language (L2). These discrimination and identification experiments examined the perception of various speech features; namely, the timing and quality of Japanese consonants, and the quality of Dutch vowels. We found that musical experience was more strongly associated with discrimination performance rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
61
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 46 publications
(60 reference statements)
9
61
1
1
Order By: Relevance
“…When comparing the above four sub-themes, a certain number of observations can be made. To start with, Sadakata and Sekiyama's (2011) results are in line with Marie et al's (2011) findings from eventrelated potentials, which measured responses to the tonal processing of the Mandarin language. Although Japanese has simpler tone systems, both studies found enhanced perceptual processing and categorization of important L2 contrasts.…”
Section: Notesupporting
confidence: 76%
See 4 more Smart Citations
“…When comparing the above four sub-themes, a certain number of observations can be made. To start with, Sadakata and Sekiyama's (2011) results are in line with Marie et al's (2011) findings from eventrelated potentials, which measured responses to the tonal processing of the Mandarin language. Although Japanese has simpler tone systems, both studies found enhanced perceptual processing and categorization of important L2 contrasts.…”
Section: Notesupporting
confidence: 76%
“…Next, the Posedel et al (2011) finding that the length of musical training within the musicians group was not correlated with pitch perception or Spanish productive phonology skills contradicts most previous findings as well as Sadakata and Sekiyama's (2011) results, as in their study the duration of training positively affected the accuracy of identification performance. This discrepancy could be explained by differing participants in the two studies- Posedel et al (2011) only accounted for the length of musical training, whereas Sadakata and Sekiyama (2011) All the participants performed equally well in the phonemic listening discrimination task.…”
Section: Notecontrasting
confidence: 55%
See 3 more Smart Citations